2020
DOI: 10.1140/epja/s10050-020-00142-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperon III: $$K^{-}p - \pi \varSigma $$ coupled-channel dynamics in the $$\varLambda (1405)$$ mass region

Abstract: Low-energy data on the three charge states in γ p → K + (Σπ) from CLAS at JLab, on K − p → π 0 π 0 Λ and π 0 π 0 Σ from the Crystal Ball at BNL, bubble chamber data on K − p → π − π + π ± Σ ∓ , low-energy total cross sections on K − induced reactions, and data on the K − p atom are fitted with the BnGa partial-wave-analysis program. We find that the data can be fitted well with just one isoscalar spin-1/2 negative-parity pole, the Λ(1405), and background contributions. In a fit with one isocsalar state, the Λ(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…[69]. In a recent update, these authors also included a second pole in their model [70]. They found that the second pole does not considerably worsen the description of the considered data but still they prefer the solution with one pole.…”
Section: Where Do We Stand?mentioning
confidence: 99%
“…[69]. In a recent update, these authors also included a second pole in their model [70]. They found that the second pole does not considerably worsen the description of the considered data but still they prefer the solution with one pole.…”
Section: Where Do We Stand?mentioning
confidence: 99%
“…This raised a debate on the one-pole versus two-pole structure of (1405) state, see, e.g., Refs. [55][56][57][58][59]. Note that the mentioned studies finding only a single pole have some deficiencies as detailed e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this context the appearance of a very detailed analysis of all available experimental data in a somewhat extended energy range together with a comprehensive compilation of the (1405) related literature has to be mentioned [24]. From our point of view this analysis is a polite rejection of any relevance of the second pole in the reproduction of data.…”
Section: About the Acceptance Of The Potentialmentioning
confidence: 99%